2020
DOI: 10.21203/rs.3.rs-33095/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low Caring Morale: A Qualitative Study of Ghanaian Pediatric Oncology Nurses’ Care Practice Challenges.

Abstract: Background: Pediatric cancer is a global problem, and some studies have highlighted that nurses in a low-income country experience work related challenges. Other studies have confirmed that nurses' caring work is often affected by several intrinsic and extrinsive factors which directly or indirectly influence the level of nurses' caring morale. But no study has explored this phenomenon among the pediatric oncology nurses in Ghana. The purpose of this study is to explore and understand the challenges that the p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Notably, we did not find any associations between nurse involvement in interdisciplinary collaboration and job satisfaction or perceived quality of care. Previous studies have demonstrated that nurses are not always considered to be part of interdisciplinary care teams and are often excluded from multidisciplinary care meetings and interdisciplinary communication 13–21 . However, nurses contribute vital insights including reports of patient's symptoms, function, perspectives, and other components of medical and psychosocial care, and are responsible for critical aspects of patient care 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, we did not find any associations between nurse involvement in interdisciplinary collaboration and job satisfaction or perceived quality of care. Previous studies have demonstrated that nurses are not always considered to be part of interdisciplinary care teams and are often excluded from multidisciplinary care meetings and interdisciplinary communication 13–21 . However, nurses contribute vital insights including reports of patient's symptoms, function, perspectives, and other components of medical and psychosocial care, and are responsible for critical aspects of patient care 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that nurses are not always considered to be part of interdisciplinary care teams and are often excluded from multidisciplinary care meetings and interdisciplinary communication. [13][14][15][16][17][18][19][20][21] However, nurses contribute vital insights including reports of patient's symptoms, function, perspectives, and other components of medical…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation